Giant RNA genomes: Roles of host, translation elongation, genome architecture, and proteome in nidoviruses - Benjamin W. Neuman; Alexandria Smart; Orian Gilmer; Redmond P. Smyth; Josef Vaas; Nicolai Böker; Dmitry V. Samborskiy; Ralf Bartenschlager; Stefan Seitz; Alexander E. Gorbalenya; Neva Caliskan; Chris Lauber (Proceedings of the National Academy of Sciences, 2025)
Positive-strand RNA viruses of the order Nidovirales have the largest known RNA genomes of vertebrate and invertebrate viruses with 36.7 and 41.1 kb, respectively. The acquisition of a proofreading exoribonuclease (ExoN) by an ancestral nidovirus enabled crossing of the 20 kb barrier. Other factors constraining genome size variations in nidoviruses remain poorly defined. We assemble 76 genome sequences of invertebrate nidoviruses from >500.000 published transcriptome experiments and triple the number of known nidoviruses with >36 kb genomes, including a 64 kb RNA genome. Many of the identified viral lineages acquired putative enzymatic and other protein domains linked to genome size, host phyla, or virus families. The inserted domains may regulate viral replication and virion formation, or modulate infection otherwise. We classify ExoN-encoding nidoviruses into seven groups and four subgroups, according to canonical and noncanonical modes of viral replicase expression by ribosomes and genomic organization (reModes). The most-represented group employing the canonical reMode comprises invertebrate and vertebrate nidoviruses, including coronaviruses. Six groups with noncanonical reModes include invertebrate nidoviruses with 31-to-64 kb genomes. Among them are viruses with segmented genomes and viruses utilizing dual ribosomal frameshifting that we validate experimentally. Moreover, largest polyprotein length and genome size in nidoviruses show reMode- and host phylum-dependent relationships. We hypothesize that the polyprotein length increase in nidoviruses may be limited by the host-inherent translation fidelity, ultimately setting a nidovirus genome size limit. Thus, expansion of ExoN-encoding RNA virus genomes, the vertebrate/invertebrate host division, the control of viral replicase expression, and translation fidelity are interconnected.